Ações regressivas: o cabimento e a crítica de uma interpretação civil do Direito Previdenciário - Chaves, Silvia Fernandes (2017)
This thesis deals with the regressive actions provided for in Article 120 of Law N. 8.213/91, as well as new regressive actions, understood as all other actions that haven‟t legal provision in the said dispositive, with a civilian look for the rule of Social Law, pointing out the flaws in the interpretation of the legal dispositive, especially with an exaggerated bias in the context of civil responsibility, that can‟t be perpetuated in a rule of Social Law